2009
DOI: 10.4103/0970-1591.52911
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional pilot study to determine the prevalence of testosterone deficiency syndrome in working population of Indian men

Abstract: Aim:To determine the prevalence of testosterone deficiency syndrome (TDS) in healthy Indian men employed in a hospital aged above 40 years.Materials and Methods:A general medical health check-up camp was organized for all male employees above 40 years age working in surgical departments. After clinical history and systemic inquiry, subjects were requested to fill the St. Louis University's ADAM Questionnaire based on which the total and free-serum testosterone estimation was then done.Results:One hundred fifty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Previously Goel et al , found 24.2% frequency of low total testosterone in Indian healthy population aged 40 to 60 years. 16 The mean total testosterone in this study was 15.92 nmol/L which is consistent with mean testosterone of 14.6 nmol/L reported by Heald et al , for Pakistani men residing in England. 17 …”
Section: Discussionsupporting
confidence: 92%
“…Previously Goel et al , found 24.2% frequency of low total testosterone in Indian healthy population aged 40 to 60 years. 16 The mean total testosterone in this study was 15.92 nmol/L which is consistent with mean testosterone of 14.6 nmol/L reported by Heald et al , for Pakistani men residing in England. 17 …”
Section: Discussionsupporting
confidence: 92%
“…As stated above, analyses of distributions and factors associated with testosterone concentrations were conducted in Europe and the United States with not much data available from the Asian region. 1,[6][7][8][9][10][11] The influence of ethnicity on testosterone concentrations is uncertain. Studies have been performed comparing testosterone concentration among Black, Hispanic, Asian and Caucasian men in United States 1,4,17,18 with some studies showing higher testosterone concentration among the Black population compared to other ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we analysed the difference in testosterone concentration among the three major ethnic groups in Malaysia. As stated above, analyses of distributions and factors associated with testosterone concentrations were conducted in Europe and the United States with not much data available from the Asian region 1,6–11 . The influence of ethnicity on testosterone concentrations is uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations